Exploring the roles of elites in managing the Chinese internet - Shoesmith, Brian (Javnost (Ljubljana), 2004)
This paper examines the issue of control of the Internet in China. We argue that the issue of control is more complex than most accounts concede. Control of a medium in China has to take into account competing interests among the political elite based in Beijing, competition between the major cities and Beijing for control of local resources and the resourcefulness of actual Internet users in China. The situation in China is compounded by the degree ofscrutiny the Chinese Internet is subjected to by foreign analysts. To understand how the Internet operates in China we argue that it is imperative to look at the role of the political elites in formulating an enacting policy.Once this approach is adopted the Chinese Internet is placed in a broader context where Chinese regulations become subject to intense pressure from elites at the central and regional levels of government. From this perspective it becomes more appropriate to talk in terms of management rather than monolithic control
Keywords: Kitajska; množične komunikacije; elektronski mediji; komunikacijska tehnologija; računalniška omrežja; internet; informacije; informiranje; nadzor